PERANCANGAN DAN PENGEMBANGAN LANSKAP SINTUNG PARK SEBAGAI AGROWISATA BERKELANJUTAN - Alfaroby, Amir; Hasan Firdaus, Muhammad; Humaina, Nahla; Aprilia, Berlian Deswan; Febriansah, Taufik; Efendi, Rahmat; Putri, Karisma; Ummah, Latifa; Aulia, Al Aini; Fajriati, Hariri; Soekartono, Soekartono (Jurnal Wicara, 2025)
Community Service Program (KKN) is a form of community service activity conducted by universities. In the KKN activities carried out in Sintung Village, Pringgarata District, Central Lombok Regency, a group of students carried out various activities with the main focus on mapping and developing village potential. This activity aims to develop Sintung Village as a sustainable landscape-based agrotourism destination. The methods used include preliminary studies, landscape design planning,and local community involvement. The results of the activity show an increase in community awareness of agrotourism potential, the formation of environmentally friendly landscape designs, and the improvement of supporting tourism facilities. The conclusion of this activity is that the development of landscape-based agrotourism in Sintung Village has great potential to improve the local economy and preserve the environment.